2015
DOI: 10.1186/s40364-015-0054-z
|View full text |Cite
|
Sign up to set email alerts
|

A meta-analysis of hypoxia inducible factor 1-alpha (HIF1A) gene polymorphisms: association with cancers

Abstract: BackgroundHypoxia inducible factor 1-alpha (HIF1A) is a transcription factor that plays important role in regulating cascade of reactions. In this study, the effect of rs11549465 (1772 C/T) and rs11549467 (1790 G/A) polymorphisms of HIF1A gene and its association with cancers were investigated through meta-analysis.MethodsMeta-analysis of genome wide association studies of HIF1A 1772 C/T polymorphism were conducted on 22 case-control studies of sample size 19024 and for 1790 G/A polymorphism 19 case-control st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 43 publications
0
18
0
Order By: Relevance
“…Genetic polymorphisms of HIF-1α or HIF-2α in human cancers have been found in previous studies (69)(70)(71)(72)(73)(74). The single nucleotide polymorphisms 1772C/T (rs11549465) and 1790 G/A (rs11549467) have been shown to be significantly associated with the overall risk of developing lung, breast, oral, prostate, cervical and renal cancers (69). Frank et al (70) demonstrated a significant association between rs2057482 in HIF-1α with the risk of rectal cancer.…”
Section: The Roles Of Hifs In Cancermentioning
confidence: 94%
“…Genetic polymorphisms of HIF-1α or HIF-2α in human cancers have been found in previous studies (69)(70)(71)(72)(73)(74). The single nucleotide polymorphisms 1772C/T (rs11549465) and 1790 G/A (rs11549467) have been shown to be significantly associated with the overall risk of developing lung, breast, oral, prostate, cervical and renal cancers (69). Frank et al (70) demonstrated a significant association between rs2057482 in HIF-1α with the risk of rectal cancer.…”
Section: The Roles Of Hifs In Cancermentioning
confidence: 94%
“…Similarly, miR-21, miR221, and miR222 family members function in oncogenesis [Hayes et al 2014]. In comparison, RUNX1 [Goyama et al 2013], TP53 [Beckerman and Prives 2010], BACH1 [Hira et al 2007], miR-193b [Yang et al 2014], and miR-124-3p ] act as tumor suppressors; and HIF1A [Anam et al 2015], PRDM14 [Nishikawa et al 2007], TRIM28 [Hatakeyama 2011], miR-15b-5p [Yang et al 2015], miR-30c-5p [Oksuz et al 2015], and miR-16-5p have been associated with various cancers.…”
Section: Regulatory Signatures: Reporter Tfs and Mirnasmentioning
confidence: 98%
“…One of them is the VEGF involved in angiogenesis. Studying samples of the tumors of head and neck squamous cell carcinoma patients having the rare homozygous allele of the 1771C>T SNP revealed increased number of micro‐vessels . Moreover, a synergistic effect was found between HIF‐1α gene polymorphisms and environmental factors such as tobacco smoking and betel nut consumption …”
Section: Discussionmentioning
confidence: 98%
“…Both are located in exon 12 in the ODD domain of the HIF‐1 gene, and they are related to the increased transactivation capacity of HIF‐1α gene . Therefore, both SNPs are usually studied together to investigate their role in the etiology of various types of cancer and other diseases such as chronic obstructive pulmonary disease and osteonecrosis …”
Section: Discussionmentioning
confidence: 99%